Space State: possible options for forming - Udartsev, S.F. (Russuin law: Theory and Practice, 2019)
The article emphasizes the role, which the space activity plays at the present stage of the evolution of the human civilization and the inevitability of its activation over the next 10-15 years. Space-related elements emerge along with others in the structure and functions of a modern developed country. Besides, the scientifi c, economic, military and other values of its space activity are increasing. In the 21 st century, the emerging states are gradually turning into one space state that coordinates and organizes not only the activity on the Earth, but the public and private activities far beyond the planet, in outer space too. Some pivotal countries have already reached the phase of this historical development of statehood. The article addresses main options of the formation of a space state: natural (nation- states and their alliances, mixed — a complex planetary state) and artifi cial which is exemplifi ed for the last several years by the emerging of unrecognized space kingdom, Asgardia. Hypothetically, it is also possible that the speed of the establishment and evolution of the space state and its forms can depend on the external infl uence coming from outer space. The options of enshrining the character of the state activity, i.e. its cosmic status, politically and legally (by means of declarations, laws, constitutions, etc.), are also considered. The author thinks that this global and irreversible trend of the formation of space statehood should be taken into account both in the political and legal doctrine and in political perspectives, long-term and middle term strategic documents and modern state development programs.
Keywords: evolution of a state; space activity; space law; a space state; formation of a space state; ways of a space state formation; natural and artifi cial ways of a space state formation; internal and external impact on a space state formation; Research Subject Categories::LAW/JURISPRUDENCE